Cross-National Longitudinal Research on Human Development and Criminal Behavior - Weitekamp, Elmar G. M. (NATO ASI Series, Series D: Behavioural and Social Sciences, 1994)
This volume is the first to bring together the work of longitudinal researchers in the field of criminology around the world. It introduces the newest research results from these projects and focuses on the newest methodological and theoretical developments in longitudinal criminological research for the study of human development and criminal behavior. The focus of the book lies on the following areas: (Multi) Problem Behavior, Age of Onset, and Paths into Delinquent and Criminal Behavior; The Problem of Determining Incidence and Prevalence in Longitudinal Research; Paths of Crime and the Relevance of Nonintervention versus Intervention; Concepts of Criminal Careers and Career Criminals; Desistance: in Search of an Explanation: Life Styles, Life Events, Coping and Aging; Theoretical and Methodological Implications of Longitudinal Research